Ulcerating Ileocolitis in Severe Amatoxin Poisoning. (18th August 2015) - Hilty, Matthias Peter; Halama, Marcel; Zimmermann, Anne-Katrin; Maggiorini, Marco; Geier, Andreas
Abstract : Amatoxin poisoning is still associated with a great potential for complications and a high mortality. While the occurrence of acute gastroenteritis within the first 24 hours after amatoxin ingestion is well described, only very few descriptions of late gastrointestinal complications of amatoxin poisoning exist worldwide. We present the case of a 57-year-old female patient with severe amatoxin poisoning causing fulminant but reversible hepatic failure that on day 8 after mushroom ingestion developed severe abdominal pain and watery diarrhea. Ulcerating ileocolitis was identified by computed tomography identifying a thickening of the bowel wall of the entire ileum and biopsies taken from the ileum and large bowel revealing distinct ileitis and proximally accentuated colitis. The absence of discernible alternative etiologies such as infectious agents makes a causal relationship between the ulcerating ileocolitis and the amatoxin poisoning likely. Diarrhea and varying abdominal pain persisted over several weeks and clinical follow-up after six months showed a completely symptom-free patient. The case presented highlights the importance to consider the possibility of rare complications of Amanita intoxication in order to be able to respond to them early and adequately.